Kajian Yuridis Terhadap Pelaksanaan Putusan Sela Yang Tertunda Tentang Upah Skorsin (Studi Kasus Perkara Nomor: 09/Pdt.Sus-PHI/PN.Tte, Jucnto Putusan Kasasi Nomor 143 K/Pdt.Sus-PHI/2015 - Thobari Thobari; Rusdin Alauddin; Nam Rumkel (Faculty of Law, Khairun University, 2020)
Termination of Employment (PHK) is basically a complex problem because it is related to unemployment, crime and job opportunities. Along with the rate of development of the business industry and the increasing number of workforce working in employment relationships, the problem of termination of employment is a problematic topic because it involves human life. The government has issued Law Number 21 of 2000 concerning Worker Unions / Labor Unions, Law Number 13 of 2003 concerning Manpower and Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes (PPHI Law) which are the basis of reference in case of layoffs . One of the problems that occurred when the Panel of Judges of PHI PN Ternate stated that the demand for wages during suspension was legal according to the law, in accordance with the provisions of Article 155 paragraph (3) of Law Number 13 of 2003 concerning Manpower so that the Panel of Judges considered the provisional demands (interlocutory decision) appropriate to was granted and sentenced the Plaintiff (Entrepreneur) to pay suspension wages to the Defendant (Worker) since November 2014 until this case has permanent legal force. However, in reality and in fact the entrepreneur / company did not implement the interim decision.